2016
DOI: 10.3329/jpsb.v6i2.27748
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Partial Splenectomy for Hypersplenism in Children with Thalassemia

Abstract: AbstructBackground: Total splenectomy, exposes children to the high risk of overwhelming postsplenectomy infections (OPSI). To avoid these adverse consequences, partial splenectomy has long been practiced for thalasseemia in children. It has been reported that the partial splenectomy keeps the child immunologically competent, hematologically stable with minimum blood transfusion and makes their life more comfortable in comparison to total splenectomy. in both groups but it was maintained at a more static fashi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…2 But for any age of thalassemic patients requiring splenectomy, partial splenectopmy leaves the option of total splenectomy open-should relapse occur. Thus, Partial splenectopmy as the initial procedure, may add some quality years to thalassemic patients of all ages before eventual total splenectomy by obviating the need for prolonged and 'difficult to follow' mandatory antibiotic prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 But for any age of thalassemic patients requiring splenectomy, partial splenectopmy leaves the option of total splenectomy open-should relapse occur. Thus, Partial splenectopmy as the initial procedure, may add some quality years to thalassemic patients of all ages before eventual total splenectomy by obviating the need for prolonged and 'difficult to follow' mandatory antibiotic prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…1 During the six months follow-up period in a study in children with thalassemia showed favorable initial results. 2 After six years of partial splenectomy, one boy of this study group presented to us for total splenectomy, at BSMMU, again with increasing need of too much blood transfusions, secondary hypersplenism and mechanical discomfort with huge splenomegaly.…”
Section: Introductionmentioning
confidence: 99%